2021
DOI: 10.1016/j.gendis.2019.09.013
|View full text |Cite
|
Sign up to set email alerts
|

miR-21a inhibits decidual cell apoptosis by targeting Pdcd4

Abstract: Decidualization of endometrial stromal cells (ESCs) accompanied with embryo implantation is a key process in mammalian reproduction. Evidence suggests that maintenance of decidual cells function is essential. As a critical part in post-transcriptional gene regulation, microRNAs (miRNAs/miR) have been confirmed to be involved in decidualization. However, whether microRNAs regulate decidual cells function has not been reported. Aiming to clarify the role and potential mechanism of miRNAs in decidual cells, artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…[ 10 ] Conversely, a decreased expression of miRNA-155-5p in decidua tissue not only promoted proliferation but also inhibited apoptosis of decidua stromal cells by inhibiting the nuclear factor kappa B signaling pathway, which could maintain normal pregnancy. [ 11 ] Li et al [ 12 ] found that miR-21a was elevated in human or mouse decidua tissues compared with endometrial tissues, which could inhibit DC apoptosis through targeting programmed cell death 4 ( Pdcd4 ). In addition, it was found that downregulated miR-346, and miR-582-3p in human placental tissues increased the migration and invasion of trophoblast cells in early pregnancy by promoting the expression of matrix metalloproteinase (MMP)-2 and MMP9 .…”
Section: Mirnas Lncrnas and Circrnas In The Establishment And Mainten...mentioning
confidence: 99%
“…[ 10 ] Conversely, a decreased expression of miRNA-155-5p in decidua tissue not only promoted proliferation but also inhibited apoptosis of decidua stromal cells by inhibiting the nuclear factor kappa B signaling pathway, which could maintain normal pregnancy. [ 11 ] Li et al [ 12 ] found that miR-21a was elevated in human or mouse decidua tissues compared with endometrial tissues, which could inhibit DC apoptosis through targeting programmed cell death 4 ( Pdcd4 ). In addition, it was found that downregulated miR-346, and miR-582-3p in human placental tissues increased the migration and invasion of trophoblast cells in early pregnancy by promoting the expression of matrix metalloproteinase (MMP)-2 and MMP9 .…”
Section: Mirnas Lncrnas and Circrnas In The Establishment And Mainten...mentioning
confidence: 99%
“…Identifying miR-21 targets has aided in understanding its mechanisms of action in the immune response. MiR-21 targets the pro-inflammatory tumor suppressor Programmed Cell Death 4 (PDCD4) after LPS stimulation, regulating IL-10 induction, and the miR-21/PDCD4 axis also is a key target in various immunological diseases [ 157 , 158 ]. MiR-21 has a role in the pathophysiology of SCI, and its expression increased following the damage, peaking on the first day and then declining [ 159 ].…”
Section: Mirna Repairs Sci By Inducing Macrophage Polarizationmentioning
confidence: 99%
“…The Pdcd4 gene encodes for a protein (programmed cell death 4) that is an inhibitor of apoptosis and is conserved across mammalian species (Li et al, 2021). Within the human endometrium, Pdcd4 expression has been identified within proliferative endometrial cells and the decidua .…”
Section: Effects Of Embryo Ploidy Status On Pdcd4 Expressionmentioning
confidence: 99%